The impact of interprofessional simulation experiences in occupational and physical therapy education: a qualitative study/ O impacto da experiência de simulação interprofissional na formação da terapia ocupacional e da fisioterapia: um estudo qualitativo - Collins, Kayla; Layne, Kelly Chamberlain; Andrea, Catherine; Perry, Lindsay Alicia (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Interprofessional experiences are an essential part of preparing occupational and physical therapy students for clinical practice. Simulation has been used to help students achieve clinical competencies, including interprofessional competencies. The following study aimed to explore the students’ perceptions of an interprofessional simulation experience, identify opportunities for the integration of interprofessional experiences across the curriculum, and document the design elements that positively influenced the outcomes of the interprofessional simulation experience. An exploratory case study design was used to examine the study aims. Focus groups were used to collect qualitative data from 85 graduate-level occupational and physical therapy students. Thematic analysis was completed on the focus group transcripts. Results from the students indicated that they perceived the interprofessional simulation experience to be beneficial to the development of affective skills and role identity. The students identified a desire for increased exposure to interprofessional education experiences throughout the curriculum. The design and implementation of the interprofessional simulation were positively received by students due to the emphasis on creating a realistic experience and despite initial student anxiety related to the experience. Interprofessional simulation is a valuable and appropriate method for engaging students in interprofessional education and developing interprofessional skills based on the results of the current study. Documenting the process of designing and implementing an interprofessional simulation may assist other programs in developing interprofessional simulation opportunities for healthcare students.